A New Variant of Newton’s Method With Fourth–Order Convergence - Jnawali, Jivandhar; Bhatta, Chet Raj (Journal of Institute of Science and Technology, 2016)
In this paper, we present new iterative method for solving nonlinear equations with fourth-order convergence. This method is free from second and higher order derivatives. We find this iterative method by using Newton's theorem for inverse function and approximating the indefinite integral in Newton's theorem by the linear combination of harmonic mean rule and Wang formula. Numerical examples show that the new method competes with Newton method, Weerakoon - Fernando method and Wang method. Journal of Institute of Science and Technology Vol. 21, No. 1, 2016, page :86-89